Comorbidities with Congenital Heart Disease among Hospitalized Children in a Specialized Cardiac Hospital in Bangladesh - Mita, Shahina Akhter; Salim, Md; Haque, Md Ataul; Shahriar, Abdullah; Zakia, Md Nazneen Umme; Salam, ABM Abdus; Rahman, AZM Raihanur; Md Jafar, Abul Hasnat (Cardiovascular Journal, 2017)
Background: Congenital heart diseases (CHD) when associated with any comorbid condition may complicate the outcome of management. So to find out and treat comorbidities before definite treatment is essential for better outcome. Methods: This observational cross sectional study was conducted in the inpatient Department of Paediatric Cardiology at National Institute of Cardiovascular Diseases, Dhaka, during the period of January 2014 to January 2015 to identify the comorbid conditions of congenital heart disease. Results: A total of 794 children with different types of congenital heart disease were enrolled during the study period. Among them, 48.6% were simple CHD and 51.4% were complex CHD. Among simple CHD, ventricular septal defect (VSD) was commonest (27.2%), Tetralogy of Fallot (TOF) occupied the second position (20.5%). One child presented with Ectopia cardis. Among complex CHD most common anomalies were VSD with either atrial septal defect (ASD) or patent ductus arteriosus (PDA) or valvular lesion. Next common anomalies were TOF with PDA or ASD &/or pulmonary valvular abnormalities. Double outlet of right ventricle (DORV) with shunt and transposition of great arteries (TGA) with shunt also occur frequently. AV canal defect with or without valvular lesion presented in significant number. Among them 616 (77.6%) had different types of comorbid conditions. Among comorbidities, respiratory and acquired cardiac comorbidities were common (37.9% & 34.1% respectively). Other congenital or genetic comorbidities were in 11.2%. Multisystem involvement was in 9.8% cases. Conclusion: Pneumonia and heart failure were the most frequent comorbid condition among both simple and complex congenital heart disease. They were common among acyanotic heart disease. But cyanotic spell, acute stroke syndrome and brain abscess were common among cyanotic heart disease. Among genetic comorbidities Downs syndrome occupied the major part. Cardiovasc. j. 2017; 9(2): 83-89